Molecular Docking of Bioactive Compounds from Gynura procumbens Against HMG-CoA Reductase as Potential Anticholesterol Agents - Iftinan Syifa Dzulfiqar; Canakya Niti Sastra; Tsalisah Rahmaniyyah Arifin; Winda Sastika; Lindawati Setyaningrum; Asa Falahi; Anies Rohman Dwijayanti; Mohammad Rofik Usman (LPPM Universitas dr. Soebandi, 2026)
Background: Hypercholesterolemia is a major risk factor for cardiovascular disease. Statins, which inhibit 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, are widely used to lower cholesterol levels; however, their use may cause adverse effects, including myopathy and rhabdomyolysis. Therefore, the discovery of natural HMG-CoA reductase inhibitors has attracted considerable attention. Gynura procumbens contains various secondary metabolites that are potentially associated with antihypercholesterolemic activity. Purpose: This study aimed to predict the potential of bioactive compounds from Gynura procumbens as HMG-CoA reductase inhibitors using an in silico molecular docking approach. Methods: A total of 58 compounds identified by LC-MS were initially screened using Lipinski's Rule of Five and ADMET prediction. Five compounds that fulfilled the selection criteria were subjected to molecular docking against HMG-CoA reductase (PDB ID: 3CCW) using AutoDock Tools 1.5.6. Protein–ligand interactions were visualized using Discovery Studio Visualizer and Molegro Molecular Viewer. The docking protocol was validated by re-docking the native ligand and evaluating the Root Mean Square Deviation (RMSD). Results: The docking protocol was successfully validated with an RMSD value of 1.48 Å using a grid box centered at (-15.927, 8.300, 44.720). Among the five selected compounds, malic acid exhibited the highest binding affinity, with a binding free energy (ΔG) of −3.81 kcal/mol and an inhibition constant (Ki) of 1.60 mM, which was the closest to that of the positive control, pravastatin. Furthermore, malic acid shared one hydrogen bond with residue ALA751 and six hydrophobic interactions with LEU853, LYS735, HIS752, LEU857, ASN755, and GLU559, indicating a binding interaction pattern similar to that of pravastatin. Conclusions: Based on the insilico analysis, malic acid was identified as the most promising bioactive compound from Gynura procumbens for inhibiting HMG-CoA reductase among the tested compounds. However, its binding affinity remained lower than that of the native ligand and pravastatin. Therefore, its biological activity should be further validated through in vitro and in vivo studies before it can be considered a potential antihypercholesterolemic agent